A new distinctive species of Barydesmus (Diplopoda, Polydesmida, Platyrhacidae) from Ecuador, with an annotated bibliographical checklist of the American Platyrhacidae - Recuero, Ernesto; Sánchez-Vialas, Alberto (Zootaxa, 2018)
Currently with 85 named species, the family Platyrhacidae in America is still poorly studied, particularly regarding Barydesmus Cook, 1896, the most diversified among the American genera. The center of diversification of Barydesmus lies in the northern third of the Andes Mountains, a megadiverse region where surely more species of these large, conspicuous diplopods await description. Here we present a new species, Barydesmus nangaritza sp. nov., easily diagnosable by the shape of the paranota, unique among the American Platyrhacidae. We provide also an updated bibliographical, annotated checklist of the whole family in America, with the aim of encouraging further studies in the group. The checklist includes the following new combinations under the genus Barydesmus: Barydesmus acanthopleurus (Hoffman, 1960) comb. nov., B. acanthosternus (Brölemann, 1900) comb. nov., B. acompus (Chamberlin, 1941) comb. nov., B. aequinoctius (Attems, 1914) comb. nov., B. affinis (Brölemann, 1919) comb. nov., B. andinus (Cook, 1896) comb. nov., B. azulae (Kraus, 1956) comb. nov., B. balsapuertus (Chamberlin, 1941) comb. nov., B. bifasciatus (Silvestri, 1897) comb. nov., B. bombonus (Chamberlin, 1941) comb. nov., B. broelemanni (Attems, 1914) comb. nov., B. brunnior (Chamberlin, 1941) comb. nov., B. celinus (Chamberlin, 1941) comb. nov., B. chuncho (Chamberlin, 1941) comb. nov., B. clathratus (Gervais, 1847) comb. nov., B. comptus Cook, 1896 comb. nov., B. contayus (Chamberlin, 1941) comb. nov., B. dunalii (Gervais, 1847) comb. nov., B. exsul (Cook, 1896) comb. nov., B. festae (Silvestri, 1897) comb. nov., B. fuscatus (Chamberlin, 1941) comb. nov., B. helophorus (Attems, 1899) comb. nov., B. incus (Chamberlin, 1941) comb. nov., B. javarynus (Schubart, 1950) comb. nov., B. leucus (Chamberlin, 1941) comb. nov., B. loretus (Chamberlin, 1941) comb. nov., B. manserichus (Chamberlin, 1941) comb. nov., B. medius (Chamberlin, 1941) comb. nov., B. obscurus (Kraus, 1955) comb. nov., B. orellanus (Chamberlin, 1941) comb. nov., B. pococki (Brölemann, 1911) comb. nov., B. retentus (Chamberlin, 1941) comb. nov., B. riparius (Carl, 1902) comb. nov., B. rufipes (Koch, 1847) comb. nov., B. scaber (Koch, 1847) comb. nov., B. socius (Chamberlin, 1941) comb. nov., B. strenuus (Silvestri, 1897) comb. nov., B. tambonus (Chamberlin, 1952) comb. nov., B. tapichus (Chamberlin, 1941) comb. nov., B. trichotypus (Chamberlin, 1941) comb. nov., B. utoquinius (Chamberlin, 1941) comb. nov. and B. zygethus (Chamberlin, 1941) comb. nov.